Nexus between nature-based solutions, ecosystem services and urban challenges - Babí Almenar, Javier; Elliot, Thomas; Rugani, Benedetto; Philippe, Bodénan; Navarrete Gutierrez, Tomas; Sonnemann, Guido; Geneletti, Davide (Land use policy, 2021)
[Display omitted] •Nature-based solutions (NBS) can mitigate some urban challenges (UC), but not all.•We study the role of ecosystem services (ES) supplied by NBS in addressing UC.•Some ES classes depend on shared factors, being commended to assess ES on bundles.•Several groups of causal relationships between UC, ES and NBS were identified.•This review confirms the NBS potential to supply multiple ecosystem services (ES). Nature-based Solutions (NBS) are increasingly promoted to support sustainable and resilient urban planning. However, design and planning urban NBS targeted at the needs of the local context require knowledge about the causal relationships between NBS, ecosystem services (ES) and urban challenges (UC) This paper aims at contributing to this knowledge, by systematically identifying nexuses (i.e. qualitative links) between UC, ES and NBS, and describing plausible causal relationships. A conceptual UC-ES-NBS criteria framework was built, and used to guide a two-step systematic literature review on current UC and on the supply of ES by urban NBS. This was followed by a non-systematic literature review, which complemented the previous one by unveiling knowledge gaps on the biophysical and social processes and attributes on which specific ES classes depend. The non-systematic review was also used to identify additional NBS. The UC review identified 18 UC and 58 sub-challenges, and illustrated which UC were more studied, according to the type of literature and environmental and socio-economic attributes of urban contexts. The ES review led to the development of an urban NBS classification, and supported the identification of UC-ES and ES-NBS nexuses, which were analysed and classified into four groups of causal relationship. For the nexuses identified as direct plausible causal relationship, the main processes and attributes on which the supply of specific ES depend were pointed out. Relationships between UC, ES, NBS, processes, and attributes were represented in the form of network diagrams. Our results can be used to support urban policies aimed at mainstreaming NBS and as a basis to further understand UC-ES-NBS relationships.